2003
DOI: 10.1046/j.1365-2141.2003.04363.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and clinical features of low‐molecular‐weight heparin‐induced thrombocytopenia

Abstract: Summary. Heparin‐induced thrombocytopenia (HIT) is a common adverse effect of unfractionated heparin (UFH) therapy. In contrast, only a few patients have been reported with HIT following low‐molecular‐weight heparin (LMWH) therapy (LMW‐HIT). To define the clinical and biological characteristics of LMW‐HIT, 180 patients treated for suspected HIT at 15 French centres were investigated. Clinical history was recorded and HIT was confirmed in 59 patients with positive serotonin release assay results: 57 of them had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 26 publications
(47 reference statements)
3
67
0
2
Order By: Relevance
“…However, there is increasing evidence that patients who have a history of clinical HIT do not show a typical anamnestic immune response when reexposed to heparin. 8,11,33 On the contrary, other reports 34,35 suggested that there might sometimes be a more rapid formation of heparin antibodies in the case of reexposure. But neither of these studies 34,35 established that their patients had had 2 distinct episodes of HIT.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…However, there is increasing evidence that patients who have a history of clinical HIT do not show a typical anamnestic immune response when reexposed to heparin. 8,11,33 On the contrary, other reports 34,35 suggested that there might sometimes be a more rapid formation of heparin antibodies in the case of reexposure. But neither of these studies 34,35 established that their patients had had 2 distinct episodes of HIT.…”
Section: Discussionmentioning
confidence: 43%
“…8,11,33 On the contrary, other reports 34,35 suggested that there might sometimes be a more rapid formation of heparin antibodies in the case of reexposure. But neither of these studies 34,35 established that their patients had had 2 distinct episodes of HIT. Moreover, 2 reports in which patients did clearly have 2 distinct episodes of serologically confirmed HIT several years apart found that the onset of thrombocytopenia during the second episode of HIT appeared to be no sooner than that observed during the first episode of HIT.…”
Section: Discussionmentioning
confidence: 43%
“…Indeed, enoxaparin and fondaparinux were administered in these four clinical trials for a mean of only approximately 7 days [19], likely contributing to the low frequency of clinical HIT observed, and rendering clinical HIT unsuitable as an end point for these analyses, especially given that HIT as a result of LMWH administration may take longer Risk factors for anti-PF4/heparin antibodies 511 to develop than HIT triggered by UFH [20]. Of interest, the single case of HIT identified (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of thrombosis without further treatment is 10-15% in 2 days, 40% in 1 week and 53% in 1 month [28][29][30][31][32][33][34][35][36]. The type of thromboembolic events is 50% DVT, 25% PE, 5-10% acute limb ischemia, 20% amputation and 3-5% acute myocardial infarction (AMI) [28][29][30][31][32][33][34][35][36]. HIT mortality may be as high as 30-50% [28][29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%